Effect of Lipodystrophy on the Quality of Life among People Living with HIV (PLHIV) on Highly Active Antiretroviral Therapy. (September 2014) - Shenoy, Archana; Ramapuram, John T.; Unnikrishan, Bhaskaran; Achappa, Basavaprabhu; Madi, Deepak; Rao, Satish; Mahalingam, Soundarya
Background: Lipodystrophy is a known adverse effect of highly active antiretroviral therapy (HAART). Lipodystrophy resulting in body dysmorphism can lower the quality of life (QoL) among HAART recipients. The main aim of our study was to find the effect of lipodystrophy on QoL among people living with HIV (PLHIV) on HAART. Methods: This cross-sectional study was conducted in a tertiary care hospital in south India. The participants were assessed for the presence of lipodystrophy. Their QoL was assessed using HIV-AIDS-targeted QoL questionnaire (HAT-QoL). Statistical analysis was carried out using SPSS version 11.5. Results: Lipodystrophy was present in 21 participants (42%). The QoL among individuals with lipodystrophy was found to be significantly lower in terms of disclosure worries ( P = .023) and financial worries ( P = .049). Conclusions: Lipodystrophy adversely affects QoL among PLHIV. There is a need for studies analyzing factors that can potentially improve the QoL in such individuals.